Rationale for and Practical Use of Sacubitril/Valsartan in the Patient’s Journey with Heart Failure and Reduced Ejection Fraction - Mauro Gori; James L Januzzi; Emilia D’Elia; Ferdinando L Lorini; Michele Senni (Cardiac Failure Review)
Sacubitril with valsartan (sacubitril/valsartan) is a relatively novel compound that has become a milestone in the treatment of patients with chronic heart failure (HF) with reduced ejection fraction (HFrEF) in the last decade. Contemporary data suggest that sacubitril/valsartan is associated with improved outcomes compared with angiotensin-converting enzyme inhibitors and angiotensin receptor blockers, and has a greater beneficial effect on myocardial reverse remodelling. Additionally, two recent trials have shown that sacubitril/valsartan is well-tolerated even in the acute HF setting, thus enabling a continuum of use in the patient’s journey with HFrEF. This article summarises available data on the effectiveness and tolerability of sacubitril/valsartan in patients with HFrEF, and provides the clinician with practical insights to facilitate the use of this drug in every setting, with an emphasis on acute HF, hypotension, electrolyte imbalance and renal insufficiency.